2021
DOI: 10.3390/ijms22042177
|View full text |Cite
|
Sign up to set email alerts
|

sFasL—The Key to a Riddle: Immune Responses in Aging Lung and Disease

Abstract: By dint of the aging population and further deepened with the Covid-19 pandemic, lung disease has turned out to be a major cause of worldwide morbidity and mortality. The condition is exacerbated when the immune system further attacks the healthy, rather than the diseased, tissue within the lung. Governed by unremittingly proliferating mesenchymal cells and increased collagen deposition, if inflammation persists, as frequently occurs in aging lungs, the tissue develops tumors and/or turns into scars (fibrosis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Noteworthy, sFasL competitive binding to Fas receptor produces anti-apoptotic and anti-cell death effects in nuclei of target cells via activation of pro-survival signaling cascades. In the decompensated liver cirrhosis group, this cellular stress response might be attenuated or abolished due to the progressive loss of function of the cells [ 46 – 48 ]. Regarding our observations on the GGT, previous studies already found GGT levels paralleled with elevated serum ferritin levels [ 49 ] to correlate with liver inflammation in patients with cirrhosis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, sFasL competitive binding to Fas receptor produces anti-apoptotic and anti-cell death effects in nuclei of target cells via activation of pro-survival signaling cascades. In the decompensated liver cirrhosis group, this cellular stress response might be attenuated or abolished due to the progressive loss of function of the cells [ 46 – 48 ]. Regarding our observations on the GGT, previous studies already found GGT levels paralleled with elevated serum ferritin levels [ 49 ] to correlate with liver inflammation in patients with cirrhosis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, considering that age represents a confounding factor in different pathologies, we cannot determine whether the blood changes are caused by the aging process itself, SARS-CoV-2 infection, or a combination of these events. While age-dependent changes in FASLG expression have already been recognized and were also linked to aging lung and respiratory disease, there are conflicting data on its active form, expression, and serum levels regarding inflammation and apoptosis [ 88 ]. Another important aspect to be disclosed is that lymphocytopenia, a common cause associated with COVID-19, could not be evaluated using the whole blood samples available from the GTEx Biobank.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis and necrosis of epithelial cells during ALI induced by SARS-CoV-2 is another important factor to consider in severe COVID-19. SARS-CoV-2 can induce cell death of lung epithelial cells by activating caspase-8, which can also contribute to immune activation through the induction of caspase-8-dependent expression of proinflammatory cytokines [50][51][52] . In addition, Fas Ligand (FasL) is an activator of caspase-8mediated apoptosis in cells that express the death receptor Fas, the receptor for FasL, and is observed on the surface of EVs in chronic lung disease [53][54][55] .…”
Section: Evs and Covid-19-associated Inflammation And Immune Responsementioning
confidence: 99%
“…SARS-CoV-2 can induce cell death of lung epithelial cells by activating caspase-8, which can also contribute to immune activation through the induction of caspase-8-dependent expression of proinflammatory cytokines [ 50 52 ] . In addition, Fas Ligand (FasL) is an activator of caspase-8-mediated apoptosis in cells that express the death receptor Fas, the receptor for FasL, and is observed on the surface of EVs in chronic lung disease [ 53 55 ] . Cells expressing the death receptor Fas may include lung epithelial cells, virally infected cells, and T-lymphocytes which are all highly implicated in COVID-19 pathophysiology, especially during ALI/ARDS [ 53 ] .…”
Section: Extracellular Vesicles As Contributors To Covid-19 Disease P...mentioning
confidence: 99%
See 1 more Smart Citation